Routine of the unpredictable: workloads and health of urgent and emergency nursing workers - Suéllen Fortes de Lima Santos Mass; Alexa Pupiara Flores Coelho Centenaro; Arlíni Fátima dos Santos; Andressa de Andrade; Gianfábio Pimentel Franco; Susane Flôres Cosentino (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To know the perceptions of nursing professionals in urgent and emergency services regarding workloads and the relationship with their health. Method: Descriptive qualitative study carried out in two urgent and emergency sectors in southern Brazil. 16 nursing professionals were interviewed. The data were subjected to thematic content analysis. Results: The first thematic category highlighted the workloads in the daily lives of professionals, highlighting Covid-19 as an element recently incorporated into the perception of biological load. The psychic load is enhanced by stress and suffering in the face of deaths, in addition to adverse working conditions. The second category showed the interface between the loads, the overload and the workers' health, highlighting the importance of the psychic load in mental health. Conclusion: Workloads are enhanced by working conditions and the relationship with the profession's work object, generating overload and risk of mental illness.